PROLOG gynecology and surgery. - AMERICAN COLLEGE OF OBSTETRICIANS AND GYNECOLOGISTS (Prolog., 2019)
Each of the 6 units of PROLOG addresses a major area in obstetrics and gynecology and consists of two partsan assessment book and a critique book. Put your knowledge to the test and earn 25 CME credits for this volume. On completion, users of this unit should be able to:Establish a differential diagnosis and screen with appropriate diagnostic tests for specific gynecologic conditionsDetermine the appropriate medical management for specific gynecologic conditions in adolescents and adult womenIdentify appropriate surgical interventions for various gynecologic conditions and strategies to prevent and treat surgical complicationsApply concepts of anatomy, genetics, pathophysiology, and epidemiology to the understanding of diseases that affect womenCounsel women regarding treatment options and adjustment to crises that may alter their lifestylesApply professional medical ethics and the understanding of medical-legal issues relative to the practice of gynecology.